O mundo Panará em criação - Werneck-Regina, Adriana (Universidade Federal de São Carlos, 2019)
The aim of this thesis is to outline ways of conceiving growth, marriage and death among the Panará, people speaking the Gê language that inhabits the Panará Indigenous Land, covering the north of Mato Grosso and southern Pará. At the same time, the contours of social relations that are configured as creation are traced, exploring how they connect to the perceptions of the growing body, the marrying body and even the body that changes when it dies. It is observed that the creation focuses on contexts of action related to the nutrition of the bodies and the relations practiced by them, involving the participation of the dead. It is discussed how the latter become constituent parts of socius. In discussing creation as a social model, it is considered how its articulation with mutual care is unstably configured, since the conflict is unveiled as inherent to the condition of existing. At the same time, it reverberates in the notion of person, indicated in it that being good and bad are powers of existences.
The Panará world in creation
Keywords: Jê; Panará; Corpo; Relações de Criação; Morte; Gê; Body; Creation Relationship; death; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA